Large‐Area 3D Hierarchical Superstructures Assembled from Colloidal Nanoparticles. Issue 18 (2nd April 2019) - Song, Guofen; Li, Jinghan; Yuan, Yang; Yao, Lulu; Gu, Jiajun; Liu, Qinglei; Zhang, Wang; Su, Yishi; Zhang, Di
Abstract: Assembling nanosized building blocks into macroscopic 3D complex structures is challenging. Here, nanosized metal and semiconductor building blocks with a variety of sizes and shapes (spheres, stars, and rods) are successfully assembled into a broad range of hierarchical (nanometer to micrometer) assemblies of functional materials in centimeter size using butterfly wings as templates. This is achieved by the introduction of steric hindrance to the assembly process, which compensates for attraction from the environmentally sensitive hydrogen bonds and prevents the aggregation of nanosized building blocks. Of these materials, Au nanostar assemblies show a superior enhancement in surface‐enhanced Raman scattering (SERS) performance (rhodamine 6G, 1506 cm −1 ) under 532, 633, and 780 nm excitation—this is 3.1–4.4, 3.6–3.9, and 2.9–47.3 folds surpassing Au nanosphere assemblies and commercial SERS substrates (Q‐SERS), respectively. This method provides a versatile route for the assembly of various nanosized building blocks into different 3D superstructures and for the construction of hybrid nanomaterials and nanocomposites. Abstract : Nanosized metal and semiconductor building blocks with various sizes and shapes are successfully assembled into a broad range of hierarchical structures in centimeter size by introducing steric hindrance to the assembly process. This method provides a versatile route for fabrication of hybrid nanomaterials and nanocomposites.